Contaminated freshwater as a Harbinger of tropical disease spread in Europe - Costa, Axelle; Guerrero, Hugo; Sureau, Aurore; Tassaint, Morgane; Augusto, Ronaldo de Carvalho (Frontiers in Environmental Science, 2024)
Human-induced environmental changes, including climate change and pollution, significantly affect host-parasite interactions, potentially altering the geographical spread and severity of various parasitic diseases. These changes may particularly influence the dynamics of diseases like schistosomiasis, posing significant public health concerns. This review explores how pollutants such as organophosphate pesticides, antibiotics, heavy metals, cities' landfills, and microplastics can affect the development and transmission dynamics of parasites, especially Schistosoma spp. Our researches highlight that pesticides promote parasitic disease development, while pharmaceuticals have mixed effects on the life cycles of these parasites. Similarly, heavy metals found in water systems disrupt host-pathogen interactions, and microplastics are linked to significant changes in snail stressor genes, a critical intermediate host for several parasites. With the rising impacts of anthropogenic activity on the environment, there is an urgent need to reassess and adjust regulatory policies to minimize these threats. By studying the implications of pollution on host-parasite interactions, we can develop better strategies for disease control and improve the preservation of our ecosystem's health.